Legal Counselling on Certificates as a Guarantee of Legal Certainty of Inheritance - Rukmono, Indra; Soediono, Riccardo; Irawan, Joni; Handayani, Tuti; Gunadi , Lie Epifani R.; Ekowati, Jeni; A. Taufiq Hidayat; Susanto, Arfian (⁠International Journal of Asia Pacific Community Service, 2024)
In land law, the word ‘land’ is used in a juridical sense, as an understanding that has been given an official limitation by the UUPA. Article 4 states that land in the juridical sense is the surface of the earth. Many things need to be considered in land sale and purchase transactions, one of which is the obligation to be made by/and sign a deed in front of a Notary/PPAT so that the transfer becomes legal and has legal certainty While Notary is regulated in Law No. 30 of 2004, it is stated that public officials are authorised to make authentic deeds and other authorities as referred to in this Law. The purpose of this activity is to provide an understanding to the community regarding the procedures for managing the sale and purchase of land in accordance with legal provisions and to increase public awareness of the importance of Notary / PPAT Deed in Land Sale and Purchase Transactions. Likewise, the enthusiasm of the residents to participate in the activity was very good and many questions arose so that the discussion became very interesting. Based on the explanation above, it can be concluded that the community service carried out in Buahan Kaja Village, Payangan District, Gianyar Regency, Bali Province has been carried out, has been in accordance with the schedule, expected goals and objectives.